2014
DOI: 10.1016/j.str.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Activation and Degradation Mechanisms of the E3 Ubiquitin Ligase Nedd4L

Abstract: We investigated the mechanisms of activation and degradation of the E3 ubiquitin ligase Nedd4L combining the available biochemical information with complementary biophysical techniques. Using nuclear magnetic resonance spectroscopy, we identified that the C2 domain binds Ca(2+) and inositol 1,4,5-trisphosphate (IP3) using the same interface that is used to interact with the HECT domain. Thus, we propose that the transition from the closed to the active form is regulated by a competition of IP3 and Ca(2+) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 40 publications
4
71
3
Order By: Relevance
“…Moreover, NEDD4L contains a C2 domain that is involved in plasma membrane association (24,25). A recent structural study suggests NEDD4L likely exhibits maximal activity when localized to membrane (26). By interaction with membrane phospholipid phosphatidylinositol 4,5-bisphosphate (PIP2), NEDD4L undergoes a conformational change, thus relieved from a self-inhibiting state (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NEDD4L contains a C2 domain that is involved in plasma membrane association (24,25). A recent structural study suggests NEDD4L likely exhibits maximal activity when localized to membrane (26). By interaction with membrane phospholipid phosphatidylinositol 4,5-bisphosphate (PIP2), NEDD4L undergoes a conformational change, thus relieved from a self-inhibiting state (26).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this PY motif is buried in the C-lobe conformation observed in all HECT domain structures solved to date, although an isolated peptide binds the NEDD4L WW3 domain as in other LPXY motif WW domain crystals (17,29). A comparison of the Nedd4 family HECT domains revealed that this PY motif and a second PY motif are conserved among multiple Nedd4 family members (Fig.…”
Section: Itch Catalytic Function Is Restrained By a Block In E2-e3mentioning
confidence: 91%
“…HECT Domain PY Motifs Are Not Sufficient for Itch Autoinhibition-It has been proposed that autoinhibition of Nedd4-2 is due to a PY motif in its HECT domain (17,28,29). Notably, this PY motif is buried in the C-lobe conformation observed in all HECT domain structures solved to date, although an isolated peptide binds the NEDD4L WW3 domain as in other LPXY motif WW domain crystals (17,29).…”
Section: Itch Catalytic Function Is Restrained By a Block In E2-e3mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, we found that Nedd4L levels steadily increased during infection and demonstrated that Nedd4L strongly interacts with TRP120 and facilitates TRP120 ubiquitination in vitro. Indeed, Nedd4L localizes primarily in the cytoplasm, where it targets proteins and receptors upon Ca 2ϩ -mediated activation (34). Our recent studies showed that Ehrlichia and TRPs stimulate intracellular Ca 2ϩ release during E. chaffeensis entry and activates the noncanonical Wnt/Ca 2ϩ pathway (6).…”
Section: Novel E Chaffeensis Ubiquitin Ligasementioning
confidence: 99%